Predicting postoperative complications of inguinal lymph node dissection for penile cancer in an international multicentre cohort. (24th March 2015) - Gopman, Jared M.; Djajadiningrat, Rosa S.; Baumgarten, Adam S.; Espiritu, Patrick N.; Horenblas, Simon; Zhu, Yao; Protzel, Chris; Pow‐Sang, Julio M.; Kim, Timothy; Sexton, Wade J.; Poch, Michael A.; Spiess, Philippe E.
<x xml:space="preserve">Abstract</x> Objectives To assess the potential complications associated with inguinal lymph node dissection (ILND) across international tertiary care referral centres, and to determine the prognostic factors that best predict the development of these complications. Materials and Methods A retrospective chart review was conducted across four international cancer centres. The study population of 327 patients underwent diagnostic/therapeutic ILND. The endpoint was the overall incidence of complications and their respective severity (major/minor). The Clavien–Dindo classification system was used to standardize the reporting of complications. Results A total of 181 patients (55.4%) had a postoperative complication, with minor complications in 119 cases (65.7%) and major in 62 (34.3%). The total number of lymph nodes removed was an independent predictor of experiencing any complication, while the median number of lymph nodes removed was an independent predictor of major complications. The American Joint Committee on Cancer stage was an independent predictor of all wound infections, while the patient's age, ILND with Sartorius flap transposition, and surgery performed before the year 2008 were independent predictors of major wound infections. Conclusions This is the largest report of complication rates after ILND for squamous cell carcinoma of the penis and it shows that the majority of complications associated with ILND are minor and resolve without prolonged morbidity. Variables pertaining to the extent of disease burden have been found to be prognostic of increased postoperative morbidity.